Antiasthmatic Effects of Sanglong Pingchuan Decoction through Inducing a Balanced Th1/Th2 Immune Response. (11th June 2018) - Zhu, Binnian; Dong, Jun; Gao, Xiangyun; He, Yanfei; Sun, Hongxiang
Abstract : Objective . To investigate the antiasthmatic effects of Sanglong pingchuan decoction (SLPCD) and to explore its mechanisms of action. Methods . The serum, bronchoalveolar lavage fluid (BALF), and lung tissues from OVA-induced allergic asthma mice were collected 24 h after the last administration. Lung pathological changes were observed by H&E staining. The inflammatory cells in BALF were counted by flow cytometry. The levels of total IgE in serum and cytokines in BALF were determined by ELISA. The expression levels of cytokine mRNA in lung were assayed by qRT-PCR. Results . SLPCD significantly inhibited airway inflammation, reduced inflammatory cells in BALF, reduced the levels of total IgE in serum and Th2 cytokines (IL-10 and IL-13) in BALF, and downregulated the mRNA expression levels of Th2 cytokines (IL-4, IL-5, IL-10, and IL-13) in lung of asthmatic mice. However, SLPCD remarkably elevated the level of Th1 cytokine IFN- γ in BALF and upregulated the mRNA expression levels of Th1 cytokines (IL-2 and IFN- γ ) in lung of asthmatic mice. Conclusion . SLPCD could attenuate airway inflammation and alleviate the pathogenesis in asthma mice through inducing a balanced Th1/Th2 response and could act as an effective drug for treatment of asthma.